Modeling Non-State Actor Interactions in Inclusive Urban Ecology: The Role of Community Gardens in Sustainable City Development - Wiranata, Indra Jaya; Simbolon, Khairunnisa (Global and Policy Journal of International Relations, 2026)
Urban areas are increasingly dealing with connected issues like environmental damage, food insecurity, and the loss of inclusive public spaces, especially in fast-growing cities like Bandar Lampung. These problems require responses that involve the community and go beyond government-led initiatives. This research looks at how community gardens, supported by groups other than the government, like local communities, regional governments, and international networks such as UCLG-ASPAC, that supports local governments in Asia-Pasific through advocacy, capacity building, and promoting inclusive sustainable development. Using examples from around the world, the study examines the urban agriculture program in Singapore, Rosario, Seoul, Seville and Yogyakarta. These cases show how community gardens can boost biodiversity, improve air quality, support food sovereignty, and create inclusive public spaces. Tropical cities, unlike those in temperate climates, can take advantage of year-round growing seasons, which opens up new possibilities for ecological innovation and local food systems. This research emphasizes that community gardens are not just green spaces; they are socio-ecological infrastructures that help strengthen urban resilience and promote justice. The involvement of groups outside the government is key to starting and expanding these initiatives. In line with Sustainable Development Goals (SDG 11, SDG 2, and SDG 13), the study concludes with practical suggestions for integrating community gardening into inclusive urban planning, particularly in tropical areas. This research provides valuable insights for policy-makers, practitioners, and international networks on creating ecologically fair and community-driven urban futures.